1999
DOI: 10.1099/0022-1317-80-3-727
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of variable regions of hepatitis C virus proteins: selection and modification of peptide epitopes to assess hepatitis C virus genotypes by ELISA.

Abstract: The immunogenicity of variable regions of hepatitis C virus (HCV) proteins was studied by ELISA by using 543 synthetic peptides from 120 variable regions and 90 sera from HCV-infected patients. Some regions from certain genotypes were less immunogenic, or even non-immunogenic, compared with their equivalents in other genotypes. However, the mean recognition of all peptides from genotypes 1a, 1b and 3 by sera infected with genotypes 1a, 1b and 3, respectively, showed no significant differences, suggesting a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 58 publications
(7 reference statements)
1
24
1
Order By: Relevance
“…In this study, we demonstrated that the carboxyterminal domains II and III of NS5A are important for priming NS5A-specific humoral immune responses. It is known that this region of NS5A contains several human B cell epitopes (53,54). Our results show that a rNS5A protein was more immunogenic in priming NS5A-specific IgG Abs compared with NS5A as a DNA plasmid.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, we demonstrated that the carboxyterminal domains II and III of NS5A are important for priming NS5A-specific humoral immune responses. It is known that this region of NS5A contains several human B cell epitopes (53,54). Our results show that a rNS5A protein was more immunogenic in priming NS5A-specific IgG Abs compared with NS5A as a DNA plasmid.…”
Section: Discussionmentioning
confidence: 52%
“…NS4B is amongthe HCV major immunogenic proteins and it is widely used in anti-HCV antibody detection in diagnostic serologic tests (6)(7)(8). Furthermore, since NS4B is a key protein in virus life cycle, it provides new opportunities for antiviral intervention against a leading cause of liver diseases worldwide (12).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the diagnostically important antigenic epitopes have been found to reside within NS4B (6)(7)(8). There are two FDAapproved commercially available enzyme immunoassays (EIA) for screening anti-HCV antibodies: Abbott HCV EIA 2.0 and ORTHO HCV Version 3.0 enzymelinked immunosorbent assay (ELISA) Test System.…”
Section: Introductionmentioning
confidence: 99%
“…The detection rate of anti-NS5 (59.3%) is much lower than the detection rates of anti-C22 (92.1%) and C33 (88.1%) (11). Commercial HCV tests based upon proteins or peptides derived solely from HCV genotype 1 may be less effective for the detection of antibody against HCV of other genotypes (8,17,24). Dow et al (10) found that sera from donors infected with different genotypes showed different patterns of reactivity by the third-generation confirmatory assay.…”
mentioning
confidence: 99%
“…Dow et al (10) found that sera from donors infected with different genotypes showed different patterns of reactivity by the third-generation confirmatory assay. As more data are accumulated, it has become increasingly evident that further improvement of HCV diagnostic tests will rely on the careful selection of sequence variants of antigens capable of detecting antibodies against different HCV genotypes with equal efficiencies.The antigenic compositions of many HCV proteins have been studied by using recombinant proteins (19) and synthetic peptides (13,24,25,26). Studies of the major HCV antigenic regions showed that sequence heterogeneity has an impact on the antigenic properties of these regions (17,19).…”
mentioning
confidence: 99%